Current molecular methods in epidemiological typing of Acinetobacter baumannii. (October 2014) - Rafei, Rayane; Kempf, Marie; Eveillard, Matthieu; Dabboussi, Fouad; Hamze, Monzer; Joly-Guillou, Marie-Laure
ABSTRACT : The emergence of Acinetobacter baumannii during recent decades as an important nosocomial pathogen responsible of worldwide, intensively documented, outbreaks has resulted in a need for effective epidemiological typing methods. Throughout the years, many typing methods for A. baumannii epidemiological studies have been proposed from phenotypic to molecular methods. Currently, the use of phenotypic typing methods have declined considerably and been progressively replaced by molecular methods. In this review, we introduce the current molecular methods available for A. baumannii typing. Each method has its own advantages and disadvantages, and the selection of an appropriate genotyping method depends on studied objectives. This review sheds light on questions in different epidemiological settings and most molecular methods used to fit these objectives.